2016
DOI: 10.7748/nm.22.10.26.s29
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nurse leadership development programme

Abstract: The challenge for nursing leaders responsible for workforce planning is to predict the knowledge, skills and abilities required to lead future healthcare delivery systems effectively. Succession planning requires a constant, competitive pool of qualified nursing leader candidates, and retention of those interested in career growth. Formal nursing leadership education in the United States is available through graduate education and professional nursing organisation programmes, such as the Emerging Nurse Leader … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 0 publications
1
56
0
8
Order By: Relevance
“…Expert consultants were invited to review KNLR programme curriculum to ensure that content was applicable to the targeted areas. This was similar to many previous studies reported in the literature (MacPhee et al., ; Martin et al., ; Paterson et al., ; Patton et al., ; Strickler et al., ; West et al., ). Timely evaluation of the leadership development programme and obtaining feedback from programme participants also provides the basis for continuing refinement and further development of the programmes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Expert consultants were invited to review KNLR programme curriculum to ensure that content was applicable to the targeted areas. This was similar to many previous studies reported in the literature (MacPhee et al., ; Martin et al., ; Paterson et al., ; Patton et al., ; Strickler et al., ; West et al., ). Timely evaluation of the leadership development programme and obtaining feedback from programme participants also provides the basis for continuing refinement and further development of the programmes.…”
Section: Discussionsupporting
confidence: 92%
“…() reported that the Developing Leader Programme, which consists of three 1‐day face‐to‐face workshops and self‐directed reflective and application activities, helped to improve self‐perceived leadership capability in junior RNs. Most recently, West, Smithgall, Rosler, and Winn () evaluated the Nurses Emerging as Leader programme and reported an improvement in developing emerging nurse leaders to prepare for leadership succession.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Learning experientially as a nurse manager should be accompanied by prior planning and close mentoring [67]. Previous studies show that the quality and level of training are responsible for orienting nurse managers towards good governance and the acquisition of the global vision of the organization [33,68,69]. Furthermore, the results of the current study emphasize how it is possible to appreciate differences between nurse managers who have completed advanced management programs with respect to others who have not participated in this type of training program, adding evidence to previous studies [68,70].…”
Section: Discussionmentioning
confidence: 99%
“…[26] A future topic for research will be to develop and test a training program for nurse managers that is independent of the organizational scale. [27] Because of constraints on the number of hospitals and participants that could be recruited for this study, there are limitations to the generalizations that can be made based on our results. Another potential limitation is that the scale and data we utilized could be outdated as they were from 2007-2008.…”
Section: Published By Sciedu Pressmentioning
confidence: 98%